Compliance of Iron Tablet Consumption and Anemia in Third Trimester of Pregnancy at Sleman Primary Health Care, Yogyakarta - Linda Yunika; Tira Alfiani Laariya; Irfan Rahmatullah (Placentum: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2025)
Background: Iron deficiency anemia in pregnant women is a global health problem with a prevalence of 36.8%, often occurring as mild anemia in the third trimester of pregnancy. In Indonesia, anemia in pregnant women reached 44.2% in 2019. In Sleman District, Yogyakarta Special Region, the prevalence of anemia in pregnant women increased to 10.46% in 2019 compared to 2015. Anemia in pregnancy causes serious complications on the maternal and the fetus. One method of preventing iron deficiency anemia in pregnancy is to take iron tablets orally. This study aims to investigate the frequency of anemia in the third trimester of pregnancy and its correlation with compliance with iron tablet consumption. Methods: This type of research is quantitative research with a cross-sectional approach. The sample of this study was all third-trimester pregnant women at the Sleman Primary Health Care who met the inclusions and exclusions, with a total of 153 respondents, using the purposive sampling technique. All the data analysis using the Spearman correlation test. Results: This study showed there was 22,22% of anemia in the third trimester of pregnancy. There was a weak negative correlation between compliance with iron tablet consumption and anemia incidence with a coefficient correlation of -0,224 with a p-value of 0,011 (p